Fecal Lipid Content, Serum Lipid Profile, and Intra-Abdominal Fat Accumulation in Normal Rats Supplemented with Rice Bran Oil - Navratilova, Hana Fitria; Damayanthi, Evy; Ardiansyah, Romadhony; Fitriyana, Intan Nur; Soejoedono, Retno Damayanti; Thenawidjaja, Maggy (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This study aimed to investigate the mechanism of rice bran oil on altering lipid absorption and blood lipid level in normal rat. Male Sprague Dawley rat age 3 months old, weighted 250–300 g were grouped into three groups: control (aquabidest 1 ml), orlistat (2.16 mg / 200 g body weight), and rice bran oil (1.04 mg γ-oryzanol / 200 g body weight). The intervention was given through oral gavage, daily for 28 days. Indicators observed were growth performance, total cholesterol and serum triglyceride levels, lipid levels in feces, and accumulation of intra-abdominal fat. The results showed that the treatment did not significantly affect body weight gain. Fecal lipid levels of orlistat, rice bran oil and control group respectively were 0.19g; 0.17g and 0.13 g (p<0.05), while the percentage of indigestible lipids for orlistat, control and rice bran oil group were 26%, 17% and 13% respectively (p<0.05). Total cholesterol and serum triglyceride levels in rice bran oil group were significantly lower than controls. Rice bran oil did not significantly affect the percentage of total intra-abdominal fat and the weight of the heart and kidney (p>0.05). The intervention of rice bran oil was shown to reduce blood cholesterol and triglyceride levels in normal mice and did not accumulate intra-abdominal fat. The results suggest that rice bran oil might have an effect on blood lipid regulation but not by preventing lipid absorption.